Amazing animal groups - Venino, Suzanne; National Geographic Society (U.S.) ([Washington, D.C.] : National Geographic Society, 1981)
Describes the behavior of animals that live in large social groups, including elephants, zebras, gorillas, wolves, prairie dogs, fishes, ants, and penguins.
Keywords: Animal societies -- Juvenile literature; Animal societies; Animals -- Habits and behavior